Convergence of the Steepest Descent Method for Minimizing Convex Functions - Abu Hassan, Malik; Monsi, Mansor; Leong, Wah June (Universiti Putra Malaysia Press, 2002)
Kiwiel and Murty (1996) discuss the convergence properties of a class of steepest descent algorithm for minimizing a continuously differentiable quasiconvex function f on mo. Under mild conditions, we prove that the limit infimum of IIVflXo)1I is zero and that false convergence does not occur even when f is convex.